THE USE OF TREND ANALYSIS IN ASSESSING FINANCIAL PERFORMANCE AT PT KIMIA FARMA TBK PERIOD 2020-2022 - Yulia eka roza; Ella Utami; Saprianto; Slamet Dermawan; Tri Deska Ramadani (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
The purpose of this study is to evaluate the financial performance of PT Kimia Farma Tbk by using trend analysis on the statement of financial position and income statement. The analysis technique in this study was carried out through a literature study, where data collection procedures were used to obtain company documents or reports related to the issues raised by researchers based on the findings of the author's estimation by utilizing trend analysis in this study, the financial performance of PT Kimia Farma Tbk in 2020 -2022 is still relatively safe even though there will still be a decline in 2020, but will experience an increase in 2021 and 2022. The company is still showing good performance, enabling it to run and operate in a way that allows its financial performance to continue improving every year.